An overview of the diagnostic and prognostic values of biochemical markers in patients with COVID-19 - Almnaseer, Zainab A.; Mohammed, Amani Naama; Al-Badran, Ihsan Mardan; Jaddoa, Hamid; Hussein, Waleed Noori (European Journal of Clinical and Experimental Medicine, 2025)
Introduction and aim. The severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has become a global pandemic that disrupts both public health operations and financial structures throughout the world. This article aims to evaluate the relationship between the severity of coronavirus disease 2019 (COVID-19) and its alterations in specific biomarkers such as D-dimer and C-reactive protein (CRP) together with alanine transaminase (ALT), aspartate aminotransferase (AST) and lactate dehydrogenase (LDH). Material and methods. Participants in this study were split into two groups consisting of 200 COVID-19 patients and 200 healthy controls ranging from 18 to 80 years old. Polymerase chain reaction and chest radiograph examinations were used to officially verify the participant’s diagnosis. This study used Mann-Whitney U tests combined with logistic regression and receiver operating characteristic (ROC) curves to identify and determine their value as diagnostic tools and prognostic indicators. Results. D-dimer and CRP along with ALT, AST, and LDH demonstrated significant and elevated levels in COVID-19 infected participants when analyzed against control participants (p<0.0001). D-dimer emerged as a diagnostic biomarker according to ROC analysis with an AUC value of 0.96 and a p-value<0.001 which signified its quality for the evaluation of the severity of the disease. The additional biomarkers AST and LDH received AUC scores of 0.79 and 0.76, respectively, with ALT reaching an AUC value of 0.74. Conclusion. The combination of the biochemical markers D-dimer, AST, and LDH significantly improves risk assessment while enhancing predictions about disease outcomes. These biomarkers provide vital data for early disease detection in combination with disease progression through tracking patient outcomes and therapeutic planning assessments.